The role of fertilizer in transforming the agricultural economy of Nepal - Pandey, Surya Prasad (International Food Policy Research Institute, 2014)
Nepal is a landlocked country, surrounded by India and China with long borders. All merchandise trade, including fertilize trade, is transited through India. Because of its geopolitical location and agroecological conditions, Nepal faces unique challenges in developing a well-functioning fertilizer market. The main objective of this policy brief is to highlight the difficulties a landlocked country faces in procuring fertilizers and the externalities it encounters from neighboring countries fertilizer polices in promoting efficient fertilizer use and supply.